2021
DOI: 10.21203/rs.3.rs-721083/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

All are equal, but some are more equal than others: Social determinants of leisure time physical activity through the lens of intersectionality

Abstract: Background To date, no research has investigated social determinants of leisure time physical activity through the lens of intersectionality in a low- and middle-income country. Therefore, the aim of this study was to explore the intersectionality in leisure time physical activity in a nationwide sample of Brazilian adults. Methods Data from the Brazilian National Health Survey conducted in 2013 were analysed (N = 58,429). Prevalence of leisure-time physical activity (150 + minutes per week in moderate-to-vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Although the current study did not look at socioeconomic status (SES), the roles of gender, race, and SES are interrelated with the combination of women, non-White, low SES being much less likely to meet PA recommendations. Mielke et al (44) found Caucasian men, in the highest quartile of income met PA guidelines 48% of the time where non-White, women, with low income only met PA 9.8% of the time. Research demonstrates a delineation in benefits conferred related to if PA is associated with leisure or occupational activities as well, with leisure PA demonstrating increased benefit where occupational activity does not offer the same benefit (45).…”
Section: Basic Sciencesmentioning
confidence: 99%
“…Although the current study did not look at socioeconomic status (SES), the roles of gender, race, and SES are interrelated with the combination of women, non-White, low SES being much less likely to meet PA recommendations. Mielke et al (44) found Caucasian men, in the highest quartile of income met PA guidelines 48% of the time where non-White, women, with low income only met PA 9.8% of the time. Research demonstrates a delineation in benefits conferred related to if PA is associated with leisure or occupational activities as well, with leisure PA demonstrating increased benefit where occupational activity does not offer the same benefit (45).…”
Section: Basic Sciencesmentioning
confidence: 99%
“…The impact of Walk or Run to Quit on cessation outcomes was comparable to other mul-ticomponent interventions [12] while also increasing physical activity among those who completed the program. Ensuring equitable access to programs like Walk or Run to Quit should be a priority given the intersections between racial/ethnic and socioeconomic disparities in both smoking [23,24] and physical activity [25,26]. In this case, subsidization did not expand the relatively narrow demographic profile of participants.…”
Section: Discussionmentioning
confidence: 99%